KAMITA: A WEB-BASED INTERACTIVE MEDIA TO INTRODUCE “KAMI” & “KITA” DIFFERENCES TO THE 1st-3rd GRADER IN SDN SAMPETAN - Adhitya Amarulloh; Rima Yunika Pratiwi; Arsyananda Rabbani (EDUCATE, 2025)
The distinction between the Indonesian pronouns "kami" and "kita" denoting exclusive and inclusive meanings, respectively is a linguistic feature not commonly found in many other languages. However, in a daily context, particularly among young generations, there has been a noticeable trend of misusing these pronouns. If this issue remains unaddressed, it may lead to a gradual decline in public understanding of the structural and grammatical concepts of the Indonesian language. In response to this concern, Kamita was developed as an interactive web-based learning platform based on Scratch, designed to improve primary school students’ comprehension and proper usage of the pronouns "kami" and "kita". This educational technology incorporates visual, auditory, animation, and interactive gaming elements to foster an engaging and informative learning experience. Scratch was selected for its capacity to simplify programming concepts through a visual block-based interface, making it particularly appropriate for educational technology aimed at young learners. Kamita is expected to serve as an innovative solution in the teaching of Bahasa Indonesia, especially in reinforcing the correct use of personal pronouns, thereby supporting the development of linguistic literacy from an early age.